EXTH-27. MOLECULAR CHARACTERIZATION AND PRECLINICAL DEVELOPMENT OF NOVEL SMALL MOLECULE INHIBITOR SPECIFIC FOR WILD-TYPE IDH1 FOR FERROPTOSIS INDUCTION IN GLIOBLASTOMA. (12th November 2021) - Murnan, Kevin; Tommasini-Ghelfi, Serena; Hurley, Lisa; Dussold, Corey; Wahl, Daniel; Stegh, Alexander
Abstract: Increased de novo synthesis, mobilization and uptake of fatty acids are required to provide sufficient lipids for membrane biogenesis in support of rapid tumor cell division and growth. In addition to their structural roles as components of the plasma membrane, fatty acid-derived lipids regulate ferroptotic cell death, a type of programmed cell death, when oxidized by iron-dependent lipoxygenase enzymes. De novo lipogenesis and the defense against oxidative lipid damage require large amounts of cytosolic NADPH. Our group has recently found that HGG up-regulate wild-type Isocitrate dehydrogenase 1 (referred to hereafter as 'wt-IDH1 high HGG') to generate large quantities of cytosolic NADPH. RNAi-mediated knockdown of wt-IDH1, alone and in combination with radiation therapy (RT), slows the growth of patient-derived HGG xenografts, while overexpression of wt-IDH1 promotes intracranial HGG growth. Isotope tracer and liquid chromatography-based lipidomic studies indicated that wt-IDH1 supports the de novo biosynthesis of mono-unsaturated fatty acids (MUFAs) and promotes the incorporation of monounsaturated phospholipids into the plasma membrane, while displacing polyunsaturated fatty acid (PUFA) phospholipids. In addition, enhanced NADPH production in wt-IDH1 high HGG increases glutathione (GSH) level, reduces reactive oxygen species (ROS), activates the phospholipid peroxidase glutathione peroxidase 4 (GPX4)-driven lipid repair pathway, and dampens the accumulation of PUFA-containing lipid peroxides, known executioners of ferroptosis. To pharmacologically target wt-IDH1, we have used and characterized wt-IDH1i-13, a first-in-class competitive α, β-unsaturated enone (AbbVie). wt-IDH1i-13 potently inhibits wt-IDH1 enzymatic activity, by covalently binding to the NADP+ binding pocket. Our data indicate that wt-IDH1i-13 promotes ferroptosis, which can be rescued by pre-treatment of cells with the peroxyl scavenger and ferroptosis inhibitor ferrostatin. wt-IDH1i-13 is brain-penetrant, and similar to genetic ablation, reduces progression and extends the survival of wt-IDH1 high HGG bearing mice, alone and in combination with RT. These studies credential to wt-IDH1i-13 as a novel therapeutic modality for the treatment of wt-IDH1 gliomas.